Severe lactic acidosis in an extremely low birth weight infant due to thiamine deficiency - MEMİŞOĞLU, ASLI; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA (WALTER DE GRUYTER GMBH, 2018)
Background: In this case report, we present a preterm newborn with persistent lactic acidosis who received total parenteral nutrition (TPN) that lacked thiamine. Case presentation: A 28-week-old, 750 g female infant was born with an Apgar score of 8 at the 5th minute. Umbilical cord blood gas levels, including lactate level, were normal, and she was admitted to our neonatal intensive care unit (NICU). Achieving full enteral feeding was not possible due to gastric residues and abdominal distention, making the patient dependent on TPN during the first 2 weeks of life. An insidious increase in lactic acid levels and uncompensated metabolic acidosis were apparent from the 23rd day of life. Severe metabolic acidosis was persistent despite massive doses of bicarbonate. The acidosis resolved dramatically within 6 h when the patient was administered with thiamine. Conclusions: Although TPN is life saving in the NICU, meticulous attention must be paid to provide all essential macro- and micro-nutrients.
Keywords: preterm; severe lactic acidosis; thiamine deficiency; TOTAL PARENTERAL-NUTRITION